Jawabanmu

2014-02-13T09:54:32+07:00
36 log (x-4) + 36 log (x+1) < 1/2

* 1/2 di jadikan bentuk log dengan bilangan pokok = 36 ->
36 log b = 1/2
          b = (36)^1/2
          b = (6²)^1/2
          b = 6
36 log (x-4) + 36 log (x+1) < 36 log 6
36 log (x-4)(x+1) < 36 log 6
36 log x²-3x-4 < 36 log 6
⇒a = 36 maka a>1 shingga penyelesaiannya
x²-3x-4 < 6
x²-3x-4-6 < 0
x²-3x-10 <0
pembuat nol
x²-3x-10 < 0
(x-5)(x+2)
*x-5 = 0
 x= 5      ∨
*x+2=0
 x=-2
syarat penyelesaian
*x-4>0
 x>4
*x+1>0
 x>-1
shingga Hp = 4 <x≤ 5